Бидистиллятор с микроволновым бойлером - Кукоба, А. В. (ХНУРЭ, 2009)
We have developed aqueous bidistiller that has the following advantages over widely used commercial setups: use of mineral water instead of tap water as a raw material, microwave water heating that prevents contact between water and the heater. Bidistiller is based on commercial microwave oven. All components that have contact with water are made of borosilicate glass. Conductivity of obtained bidistilled water is about 1.6 pS/cm
Keywords: бидистиллятор; микроволновый бойлер